2012
DOI: 10.1097/wad.0b013e318231e6c7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetic Analysis of the APP, PSEN1, and PSEN2 Genes in Finnish Patients With Early-onset Alzheimer Disease and Frontotemporal Lobar Degeneration

Abstract: Mutations in 3 genes, amyloid precursor protein (APP), presenilin 1 (PSEN1), and presenilin 2 (PSEN2), have been identified as causing a proportion of early-onset Alzheimer disease (eoAD) cases. A few PSEN mutations have also been previously detected in patients with frontotemporal lobar degeneration (FTLD). In order to evaluate the role of these genes in a clinical series of Finnish eoAD and FTLD patients, we sequenced exons 16 and 17 of the APP gene and the coding regions of the PSEN1 and PSEN2 genes in 140 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 44 publications
0
15
1
Order By: Relevance
“…However, the facts that it did not appear to segregate with AD in the families of the carriers, nor did it affect the Aβ42/Aβ40 ratio in an in vitro assay, and it was also found in healthy controls suggest that it is likely a benign mutation [10,20,28]. Interestingly though, the brain biopsy of the patient in our study revealed AD-type neuropathology.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…However, the facts that it did not appear to segregate with AD in the families of the carriers, nor did it affect the Aβ42/Aβ40 ratio in an in vitro assay, and it was also found in healthy controls suggest that it is likely a benign mutation [10,20,28]. Interestingly though, the brain biopsy of the patient in our study revealed AD-type neuropathology.…”
Section: Discussioncontrasting
confidence: 54%
“…The C9orf72 hexanucleotide repeat expansion or MAPT and GRN mutations underlie the majority of the familial FTLD [5,6]. In Finland, the prevalence of the C9orf72 repeat expansion is exceptionally high [7], whereas MAPT and GRN mutations associated with FTLD or PSEN1, PSEN2 and APP mutations associated with AD have been found to be very rare [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…microtubule-associated protein tau, MAPT) may explain the mixed type of neuropathology, but a combination of 2 pathogenic mutations in 1 person is rare [26]. The influence of other pathogenic mutations is unlikely in the present study, because our previous studies have shown that mutations in MAPT or progranulin are rare or absent in the Finnish population [27,28,29,30]. The disease process and neurodegeneration itself can also be reflected on AD biomarker values [31].…”
Section: Discussionmentioning
confidence: 79%
“…Only a few PSEN1 variants have been reported in Finnish AD families: two families carry the 'Cotton-wool' variant, Δ9Finn (c.869_955del) [45], p.(Met146Val) has been reported in a Swedish family of Finnish descent [46,47] and p. (Pro264Leu) in one family [48]. Screening of APP, PSEN1 and PSEN2 in a cohort of 140 EOAD patients revealed no variants that might affect function [49]. In addition, duplication of APP was not detected in a cohort of 64 Finnish EOAD patients [50].…”
Section: Discussionmentioning
confidence: 99%